Crack Depth Measurement of Reinforced Concrete Beams Using UPV - Ari Wibowo; Hendro Suseno; M. Hamzah Hasyim; Roland Martin S.; Christin Remayanti N.; Ardian Prima K. (Department of Civil Engineering, Faculty of Engineering, University of Brawijaya, 2014)
Cracks in the concrete should not be ignored because it can cause serious problems. Cracks in concrete usually terms only in wide of rift, so a review of crack depth is needed. Crack depth can be measured by Ultrasonic Pulse Velocity (UPV). UPV test is one of the Non Destructive Tests on the building. UPV testing is influenced by several factors such as reinforced steel. The aim of this study is to determine the accuracy of crack depth in reinforced concrete beams with a thickness of concrete cover measured by UPV. Four variations of 15 concrete beams and one variation of unreinforced beam with thick concrete cover are used in this study. Three test specimens are used for each variation. The thickness of concrete cover is measured at point of 2 cm, 3 cm, 4 cm, and 5 cm. The concrete beams of 15 x 20 x 50 cm in size were designed with 8 cm crack depth. Artificial crack in the concrete beam is generated in a way to give the sealing of cracks in the aluminum zinc plate formwork before casting occur. Crack protection removed from the formwork with duration of 3-4 hours after casting. Crack depth measured by UPV test is done after 28 days concrete age. The results showed that there is a relative error of crack depth measured with UPV test. The average relative error of concrete with a thickness cover of 2 cm, 3 cm, 4 cm, and 5 cm was respectively 6.80 %, 6.63 %, 5.48 % and 4.91 %. The average relative error of unreinforced concrete was 4.59 %. Statistical analysis with one way F test shows that there is no significant difference between the relative error of crack depth measured with UPV test at each cover depth variation and unreinforced concrete with α = 0.05.